The gut microbiome and Alopecia areata: Implications for early diagnostic biomarkers and novel therapies - Kang, Yongbo; Cai, Yue; Zhao, Yanqin; Yang, Ying (Frontiers in Nutrition, 2022)
Alopecia areata (AA) accounts for the autoimmune disorder mediated by T cells, whose prognostic outcome can not be predicted and curative treatment is unavailable at present. The AA pathogenic mechanism remains largely unclear, even though follicular attack has been suggested to result from that attack of immune privilege-losing hair follicles driven by immunity. Recently, gut microbiota is suggested to have an important effect on immunoregulation under autoimmune situations like AA. Fecal microbial transplantation (FMT) may be used to treat AA. Nonetheless, related research remains at the initial stage. To promote the rapid progress of relevant research, the present work aimed to shed more lights on gut microbiota’s effect on AA, early diagnostic biomarker and FMT therapeutics.